2009
DOI: 10.1007/s00268-009-9959-8
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the Evidence Base for Trauma Quality Improvement: A Collaborative WHO‐IATSIC Review

Abstract: Trauma QI programs are consistently shown to improve the process of care, decrease mortality, and decrease costs. Further efforts to promote trauma QI globally are warranted. These findings support the further development and promulgation of the WHO-IATSIC Guidelines for Trauma QI Programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 71 publications
0
46
0
Order By: Relevance
“…However, the aim of this study was to assess the current level and form of implementation, rather than to establish the evidence-base for QI programs, as this has been previously reported. 7 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the aim of this study was to assess the current level and form of implementation, rather than to establish the evidence-base for QI programs, as this has been previously reported. 7 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, increased publication of successful examples of QI from LMICs should be prioritized in order to motivate providers, and provide models for future programs. 7,35,36 Nationally, the authors propose that a preventable death in a young victim of trauma should be just as “anathema” as a maternal death, with mandatory reporting to the ministry of health, and thus with a similar health system prioritization of excellence in care provided to victims of trauma. On a global scale, there is a need for increased dissemination of QI programs as a means of empowering local providers to participate in their health systems as planners, system-thinkers, and as agents for change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To bring about positive behavioral changes, attention should be directed towards young people before they are actually allowed to drive 67. The aim of this review is to discuss the magnitude of the problem of road traffic accidents (RTAs) in Saudi Arabia and suggest the establishment of a trauma care system as a solution to improve trauma outcomes 810…”
mentioning
confidence: 99%
“…Studies have shown that injury-related mortality is twice the expected rate in multiple Indian hospitals (Deshmukh et al, 2012;Murlidhar & Roy, 2004). Trauma quality improvement programs that rely on trauma registries have been shown to be effective in improving care, decreasing mortality, and reducing cost (Juillard, Mock, Goosen, Joshipura, & Civil, 2009).…”
Section: Introductionmentioning
confidence: 99%